Approach to Fractal Geometry in the Mathematics Degree (Revista BOEM, 2025)
This experience report explores the study of Fractal Geometry as a possible application in Basic Education. The activity was carried out as part of the Mathematics Education Trends course in the Mathematics Teaching Degree Program at the Federal Institute of Education, Science and Technology of Rio Grande do Sul, Caxias do Sul Campus. The purpose of this report is to discuss the reasons for using Fractal Geometry in the classroom and to present a possible way to implement it. Unlike Euclidean Geometry, which is often associated with human-made structures, Fractal Geometry is connected to nature, which serves as a motivation for its study. During the teaching activity, the concept of fractals was explored together with the undergraduate students, and a hands-on activity involving the manual construction of fractals using a ruler, set square, and compass was conducted. Applications of fractals in nature were presented, and the calculation of dimensions—using concepts of exponentiation and logarithms—was also explored. To conclude the activity, students created fractals with the help of GeoGebra software. The practice was developed and reflected upo
Keywords: fractal geometry; basic education; high school